THE DARK SIDES OF SCIENCE IN KAZUO ISHIGURO NEVER LET ME GO - Rosa Maria Simamora; Tasiana Indun Nainggolan (Muse: Jurnal of Art, 2024)
This thesis describes the dark sides of science in Kazuo Ishiguro's Never Let Me Go. In this novel, Ishiguro clearly presents Kathy, the novel’s main character, as a representation of people who become the victims of the dark sides of science by Madame, Miss Lucy, and Miss Emily end in dying. This study uses narrative qualitative research and applies literary sociology theory by Wellek and Warren saying that the work of literature, the purpose as well as the things that are implicit in the work itself and that are related to social problems. The analysis is focused on alienation and exploitation as the dark sides of science and technology. In this study, there are two concepts of alienation. The people who alienate others are represented by Madame, Miss Lucy, and Miss Emily towards the characters Kathy, Ruth, and Tommy. The people who are alienated are represented by Kathy, Ruth, and Tommy who are placed by figures as representatives of the government or companies who agree with the development of science and technology, who are cloned in a Hailsham dormitory with strict rules that are lonely and hopeless. Exploitation in this study is represented by the characters Kathy H, Ruth and Tommy carried out by Madame, Miss Lucy, and Miss Emily who act as if they are educating and looking after the clones even though they are representatives of the authorities to ensure that the clones are in a healthy condition until time for donation. The clones, Kathy H, Ruth, and Tommy are exploited by strange and strict rules, hopeless, cruel, and are not allowed to become parents because the most important thing is their body organs without regard for their humanity. The study concludes that Kazuo Ishiguro in Never Let Me Go conveys the dangerous dark side of science to people i.e. alienation, and exploitation.